(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: Glycemic control is the main therapeutic goal for the prevention of diabetes related complications. However, achieving optimal glycemic control on long term basis among patients with Type 2 diabetes remains challenging in developing countries like Bangladesh. The purpose of the study to determine the factors associated with glycemic control among patients with Type 2 diabetes at Chittagong Medical College Hospital, Chattogram, Bangladesh. Materials and methods: This cross sectional study included 120 patients with Type 2 diabetes aged 40-75 years who attended at Outpatient Department of Endocrinology, Chittagong Medical College Hospital between July 2020 to June 2021. Important variables in this study were socio-demographics, fasting blood glucose, HbA1c, BMI, waist circumference, duration of DM, proteinuria and documented history of chronic complications. Patent’s HbA1c were categorized into good glycemic control <7% and poor glycemic control ³7%. Results: 84.2% of the patient’s had poor glycemic control. The mean (±SEM) BMI, waist circumference, SBP, DBP, HbA1c and FBG were significantly higher in patients with poor glycemic control. Majority of patients with poor glycemic control were female and ³60 years old. Patients with a history of higher BMI (65.3%), waist circumference (85.1%), 10 years of diabetes (33%), combination of OHA and insulin (42.6%) had poor glycemic control. There was no significant association with glycemic control and family history of diabetes, history of smoking, other socio-demographic variables. Patients without complications and proteinuria had significantly better glycemic control. Conclusion: The proportion of patients with poor glycemic control was high. Age, duration of diabetes, obesity, anti-diabetic agents and complications were associated with glycemic control. JCMCTA 2022 ; 33 (1) : 132-137